ANALISIS YURIDIS PENGEMBALIAN KERUGIAN KEUANGAN NEGARA DALAM TINDAK PIDANA KORUPSI PENYELEWENGAN DANA DESA (STUDI PUTUSAN NOMOR 74/ PID.SUS-TPK/2022/PN.BNA) - Delfiandi, Delfiandi; Mulyadi, Mahmud; Trisna, Wessy (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2024)
Abstract: Restoring state financial losses due to corruption is a reform step that needs to be implemented. The research formulation of this thesis is the concept of recovering state financial losses in cases of criminal acts of corruption based on the anti-corruption legal regime in Indonesia; whether the return of state financial losses in the criminal act of corruption in misappropriation of village funds by the Village Head can be considered as a reason to remove the corruption crime if it is carried out before the investigation; and what is the analysis of the judge's considerations and decisions that sentenced the accused Village Head even though he had recovered state financial losses in the Banda Aceh District Court decision Number 74/Pid.Sus-TPK/2022/PN-BNA. This type of research is normative legal research, descriptive in nature. The approaches used are the statutory approach and the case approach. The data used is secondary data, which was collected using library study data collection tools, using document study techniques. Methods of qualitative data analysis and deductive conclusion drawing. The research results concluded that the concept of returning state financial losses in the anti-corruption legal regime in Indonesia is an effort to uphold justice. Keywords: Corruption, Recovery Of State Financial Losses, Village Funds Abstrak: Mengembalikan kerugian keuangan negara akibat korupsi merupakan langkah reformasi perlu diberlakukan. Rumusan penelitian tesis ini yaitu bagaimana konsep pengembalian kerugian keuangan negara dalam perkara tindak pidana korupsi berdasarkan rezim hukum anti korupsi di Indonesia; apakah pengembalian kerugian keuangan negara dalam tindak pidana korupsi penyelewenangan dana desa oleh Kepala Desa dapat dianggap sebagai alasan untuk menghapus pidana korupsi jika dilakukan sebelum penyidikan; dan bagaimana analisis pertimbangan dan putusan hakim yang menjatuhkan hukuman terhadap terdakwa Kepala Desa meskipun telah mengembalikan kerugian keuangan negara dalam putusan Pengadilan Negeri Banda Aceh Nomor 74/Pid.Sus-TPK/2022/PN-BNA. Jenis penelitian ini adalah penelitian hukum normatif, bersifat deskriptif. Pendekatan yang digunakan adalah pendekatan perundang-undangan dan pendekatan kasus. Data yang digunakan adalah data sekunder, yang dikumpulkan dengan alat pengumpulan data studi pustaka, dengan teknik studi dokumen. Metode analisis data kualitatif dan penarikan kesimpulan secara deduktif. Hasil penelitian disimpulkan bahwa konsep pengembalian kerugian keuangan negara dalam rezim hukum anti korupsi di Indonesia merupakan upaya untuk menegakkan keadilan Kata kunci: Dana Desa, Korupsi, Pengembaian Kerugian Negara